DMT1 Expression and Iron Levels at the Crossroads Between Aging and Neurodegeneration - Ingrassia, Rosaria; Garavaglia, Barbara; Memo, Maurizio (Frontiers in Neuroscience, 2019)
Iron homeostasis is an essential prerequisite for metabolic and neurological functions throughout the healthy human life, with a dynamic interplay between intracellular and systemic iron metabolism. The development of different neurodegenerative diseases is associated with alterations of the intracellular transport of iron and heavy metals, principally mediated by Divalent Metal Transporter1 (DMT1), responsible for Non Transferrin Bound Iron transport (NTBI). In addition, DMT1 regulation and its compartmentalization in specific brain regions play important roles during aging. This review highlights the contribution of DMT1 to the physiological exchange and distribution of body iron and heavy metals during aging and neurodegenerative diseases. DMT1 also mediates the crosstalk between central nervous system and peripheral tissues, by systemic diffusion through the Blood Brain Barrier (BBB), with the involvement of peripheral iron homeostasis in association with inflammation. In conclusion, a survey about the role of DMT1 and iron will illustrate the complex panel of interrelationship with aging, neurodegeneration and neuroinflammation.